2022
DOI: 10.3390/su14148424
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Plant-Based Milk Alternatives Part 2: Environmental Impacts

Abstract: Human food production is the largest cause of global environmental changes. Environmental benefits could be achieved by replacing diets with a high amount of animal-sourced foods with more plant-based foods, due to their smaller environmental impacts. The objective of this study was to assess the environmental impacts of the three most common plant-based milk alternatives (PBMAs)—oat, soy, and almond drink—in comparison with conventional and organic cow milk. Life cycle assessments (LCA) were calculated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Summaries of GHGe [ 64 - 67 , 69 - 78 68 ••, ] and water use [ 66 , 67 , 71 , 72 , 75 , 77 , 79 68 ••, ] comparing plant-based milks to cow’s milk, compiled from life cycle assessment studies, are shown in Fig. 3 and Table 3 (see Table S4 for study details).…”
Section: Environmental Impacts Of Dairy and Plant-based Milksmentioning
confidence: 99%
See 3 more Smart Citations
“…Summaries of GHGe [ 64 - 67 , 69 - 78 68 ••, ] and water use [ 66 , 67 , 71 , 72 , 75 , 77 , 79 68 ••, ] comparing plant-based milks to cow’s milk, compiled from life cycle assessment studies, are shown in Fig. 3 and Table 3 (see Table S4 for study details).…”
Section: Environmental Impacts Of Dairy and Plant-based Milksmentioning
confidence: 99%
“…Comparing water use associated with producing plant-based milks is complicated by the wide range of metrics used in the literature. Studies in our review measured blue water footprint (WF), i.e., freshwater withdrawals from ground and surface sources lost to evaporation or incorporated into the product, such as for irrigation [ 66 , 75 , 79 68 ••, ]; total WF, a combined measure of blue, green (rainwater available to plants), and grey (polluted) water [ 77 , 79 ]; and water withdrawals, which include all freshwater drawn from a source regardless of whether it returns to the watershed after use [ 71 ]. Some studies also weighted water use by the level of scarcity in the region from where it was withdrawn, for example, withdrawals from a water-scarce region such as California were weighted more heavily [ 67 , 72 , 77 , 80 68 ••, ].…”
Section: Environmental Impacts Of Dairy and Plant-based Milksmentioning
confidence: 99%
See 2 more Smart Citations
“…While soy, oat, almond, and rice, beverages were once a niche health food store market, the 2022 sales of these products exceeded US $3.1 billion dollars in the United States and US $20.9 billion globally [207]. Although at first glance such beverages appear to be superior to dairy milk in terms of environmental impact, such might not be the case when nutritional factors (protein and various nutrients) are brought into the assessment [208][209][210]. Almond milk, the number one dairy beverage alternative in the US, utilizes significant quantities of water during manufacturing [211].…”
Section: Dietary Displacement Planetary Healthmentioning
confidence: 99%